Engineering Evaluation of Self-Combustion Prevention and Stockpile Management Optimization at PT. Kuansing Inti Makmur - Anaperta, Yoszi Mingsi; Frinaldi, Aldri; Rembrant, Rembrant; Lanin, Dasman; Umar, Genius; Octova, Adree; Fitri, Lira Zana; Putra, Kyrie Eleison (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2025)
This study looks into the thermal risks and ways to deal with them that come with coal self-combustion at the Alam Barajo stockpile, which is run by PT. Kuansing Inti Makmur. Three coal piles: UHS 12F (±2 months), UHS 01A (±1 month), and Medium 11C (±3 months), were monitored to see how the length of time they were stored and how often it rained affected the temperature rise and the subsequent quality loss. The results reveal that the temperature of the pile rises dramatically with extended storage. For example, UHS 12F had a daily rise of 5.04°C, while UHS 01A saw a rise of 1.65°C. Self-combustion in Medium 11C reached a high of 222.1°C, which caused the ash content to rise by 2.62% and the calorific value to drop. Heavy rain made the temperatures drop for a short time, which suggests that evaporative processes caused the cooling. The study shows that present ways of managing stockpiles, especially the FIFO technique, are not being used to their full potential. To reduce the risk of combustion and keep the quality of the coal, engineers advocate making changes like regular temperature monitoring, correct compaction, covering with tarps, and distributing the coal before it catches fire.